1990
DOI: 10.1159/000110783
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Study of Neurological Disorders in Rural Central Ethiopia

Abstract: Between 1986 and 1988 a door-to-door survey was conducted on a stable rural population of 60,820 in central Ethiopia. Trained lay health workers made a complete census and identified cases with symptoms -and signs of neurological disorders, using specially designed questionnaires which, in a previous pilot study, were found to have a sensitivity of 91% and specificity of 85%. Neurological disorders in the rural population were epilepsy, postpoliomyelitis paralysis, mental retardation, peripheral neuropathy (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
2
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 15 publications
4
90
2
1
Order By: Relevance
“…Our findings confirm high prevalence rates of epileptic seizures/epilepsy in the hospital and the community, which agrees with the results of previous epidemiological studies of epilepsy in sub-Saharan Africa [5,6,9,[13][14][15][16][17][18][19]. Most studies conducted in parts of Africa and Latin America indicate higher prevalence rates of epilepsy than have been found in high-income countries, but these prevalence rates can vary within a single country, as shown in Benin, the Ivory Coast, Senegal and Tanzania [6,9,19].…”
Section: Prevalence Of Epilepsy In Sub-saharan Africasupporting
confidence: 92%
“…Our findings confirm high prevalence rates of epileptic seizures/epilepsy in the hospital and the community, which agrees with the results of previous epidemiological studies of epilepsy in sub-Saharan Africa [5,6,9,[13][14][15][16][17][18][19]. Most studies conducted in parts of Africa and Latin America indicate higher prevalence rates of epilepsy than have been found in high-income countries, but these prevalence rates can vary within a single country, as shown in Benin, the Ivory Coast, Senegal and Tanzania [6,9,19].…”
Section: Prevalence Of Epilepsy In Sub-saharan Africasupporting
confidence: 92%
“…Some researchers developed questionnaires for their study but provided inadequate information on psychometric properties of the instruments. 12,25,30,34,36,47 The instruments gathered information on signs and symptoms of various disorders 25 and qualitative information on a child's social integration into society, 47 attitude of families toward their disabled children, 43,58 hearing ability, 30,34 and availability of human resources to provide service for disabled children. 36 Some of the researchers provided limited information on characteristics of the questionnaires and also compared them to more standard tools.…”
Section: Screening Methodsmentioning
confidence: 99%
“…14,25,48,89,92 The rates generally varied between 0.1% 48 and 0.4% 92 except for 1 study, 89 which reported a rate of 62.2%. All the studies except the study by Chen and Simeonsson 14 used a 2-stage design.…”
Section: Motor Disabilitiesmentioning
confidence: 95%
See 1 more Smart Citation
“…And people's belief that epilepsy is contagious and thus hesitate to help or touch the person who has fallen during a seizure. Thus, those suffering from epilepsy are stigmatized and ostracized in the belief that their condition is a demonic possession and believed to be contagious consequently lead epileptic patients to develop different psycho-social problem such as perceived stigma and psychiatric illness which affect epileptic patients more than the seizure itself [1][2][3][4][5] . Stigma is typically a social process, experienced or anticipated and characterized by exclusion, rejection and blame or devaluation about a person or group 6 .…”
Section: Introductionmentioning
confidence: 99%